Utilization meta-analysis to identify the convenience of eBooks (visual and audio) for learning - Mailool, Jefri; Arlinwibowo, Janu; Linguistika, Yulia (International Journal of Electrical and Computer Engineering (IJECE), 2025)
This research aims to conclude the influence of eBooks in the learning process throughout the world. The meta-analysis design taken was a group contrast between control and experimental groups with a random effect size model. The criteria used are time “data published 2018–2023,” published in English, type of publication is a quantitative research article, the research design is a difference between control and experimental groups, containing complete data “mean, sample size, and standard deviation,” and recorded in the Scopus database. Data collection was guided by the PRISMA method. The results of the analysis showed that the data were heterogeneous and free from publication bias. The results of the analysis showed that there was a large “positive” effect as indicated by a p-value <0.001<5% “95% confidence interval” and a total effect size=0.86 [0.61; 1.11]. It can be concluded based on the latest findings that eBooks have an equally good effect on all conditions which are influenced by the type of competency developed, the eBook information base, the type of eBook, and class size.